A newly recognised Australian endemic species of Austrolecanium Gullan & Hodgson 1998 (Hemiptera: Coccidae) from Queensland - Lin, Yen-Po; Ding, Zheng Yee; Gullan, Penny J.; Cook, Lyn G. (Zootaxa, 2017)
Austrolecanium cryptocaryae Lin & Cook sp. n. is described based on adult female morphology and DNA sequences from mitochondrial and nuclear loci. This Australian endemic species was found on the underside of leaves of Cryptocarya microneura (Lauraceae) in Queensland. All phylogenetic analyses of four independent DNA loci and a concatenated dataset show that A. cryptocaryae is monophyletic and closely related to A. sassafras Gullan & Hodgson, the type species of Austrolecanium Gullan & Hodgson. The adult female of A. cryptocaryae is described and illustrated and a table is provided of the characters that differ among adult females of the three species of Austrolecanium currently recognised (A. cappari (Froggatt), A. cryptocaryae sp. n. and A. sassafras).